Pelaksanaan Olahraga Arung Jeram di Sungai Batang Sangir Kabupaten Solok Selatan - Anton Komaini; Andri Gemaini; Andi Syaputra (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2018)
The purposes of this study are to know how the implementation of rafting and the condition of rafting natural resources in south solok regency. This is descriptive research. This research was conducted in rafting area in batang sangir river south solok regency on may until june 2018. The population were administrators, societies and visitors. The sampling technique was done by interviewing 20 people as samples. Data collection included interview, observation and documentation. Qualitative method was used in data analysis. The results of the research as follows: 1) batang sangir south solok has length of rafting track around 25km in grade II, III and even grade IV in high rainfall weather. 2) human resources or rafting management in south solok regency is not good. 3) the facilities and infrastucture of rafting in south solok are inadaquate with only 1 inflatable boat available and 2 inflatable boats as loan. The transportation and road are good for motorcycles and cars. Keyword. Rafting, Sungai Batang Hari